THE RELATIONSHIP BETWEEN YIELD AND PATHOGENS ATTACK ON THE ADVANCED BREEDING WINTER WHEAT LINES ASSESSED FOR ADULT PLANT RESISTANCE - Gabriela PĂUNESCU; Mirela PARASCHIVU; Ramona Aida PĂUNESCU; Cătălin Aurelian ROȘCULETE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
During 2021-year, 155 wheat lines in various stages of breeding process were assessed in microcultures for adult plant resistance on the pathogens attack and the relationship with yielding capacity. The wheat lines Ursita and Voinic were considered as control cultivars. The assessment was performed under natural infection conditions, without the application of fungicides. The wheat lines were scored, depending on adequate scales: - Helminthosporium leaf blotch (Helminthosporium tritici repentis) - modified scale 0-9 was used for pathogens that produce leaf spots; - Septoria leaf blotch (Zymosptoria tritici sin. Septoria tritici) - the scale developed by Vrapi et al. (2012) – Septoria glume blotch (Parastagonospora nodorum - syn. Stagonospora nodorum; Septoria nodorum; Phaeosphaeria nodorum; Leptosphaeria nodorum) - the Bronnimann scale was used (1968); - Powdery mildew (Blumeria graminis f.sp.tritici sin. Erysiphe graminis) - the Saari-Prescot scale was used (1975); Leaf rust (Puccinia recondita f.sp.tritici) - the Cobb's scale modified by Peterson was used (Peterson et al., 1948). For Helminthosporium tritici repentis, the most relevant pathogen, the attack distribution showed that most of the tested material - 32.9% was at note 3 and the lowest - 1.3% at note 6. The correlation between yield and attack of reticular spot of wheat leaves was noticed (r = −0.14), but not significant (the coefficients being below 0.16 - the value from which the correlation could be considered significant at P = 5%). The fact that the other pathogens attacked less in the conditions in which they were present and the distribution of notes for Helminthosporium tritici repentis was mainly between 1-3 notes interval, suggests that the new breeding material showed a good adult plant resistance in natural infections in pedological and climatic conditions from Caracal Research Station.